African American religion and the civil rights movement in Arkansas - Williams, Johnny E. (University Press of Mississippi, 2003)
Civil Rights -- Religious History-- & What role did religion play in sparking the call for civil rights? Was the African American church a motivating force or a calming eddy? The conventional view among scholars of the period is that religion as a source for social activism was marginal, conservative, or pacifying. Not so, argues Johnny E. Williams. Focusing on the state of Arkansas as typical in the role of ecclesiastical activism, his book argues that black religion from the period of slavery through the era of segregation provided theological resources that motivated and sustained preachers.